2019
DOI: 10.1007/s42729-019-00084-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Fractions and Availability of Zn in a Calcareous Soil in Response to Biochar Amendments

Abstract: Availability of Zinc (Zn) is very low in calcareous soils and hence, an amendment must be used to increase Zn availability to plants. The main objective of this study was to assess the changes in chemical fractions and availability of Zn in a calcareous soil amended with corn residue biochar. Three corn residue biochars were produced at 200 (B200), 350 (B350), and 500°C (B500) and applied at 1 and 2% w/w to a calcareous soil with low organic C content (4.1 g kg −1) and high pH (7.7). The mixtures were incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Ahmad et al (2014) reported that the high immobilization of PTEs in biochar-amended soils was mainly due to the presence of mineral oxides and OM in biochar, which coprecipitated and made inner-sphere complexes with PTEs. Similar to the current study, other studies indicated that biochar concentration of PTEs bounded to OM in calcareous soil increased with the addition of different biochars (Boostani et al 2019;Kabiri et al 2019;Karimi et al 2019).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Ahmad et al (2014) reported that the high immobilization of PTEs in biochar-amended soils was mainly due to the presence of mineral oxides and OM in biochar, which coprecipitated and made inner-sphere complexes with PTEs. Similar to the current study, other studies indicated that biochar concentration of PTEs bounded to OM in calcareous soil increased with the addition of different biochars (Boostani et al 2019;Kabiri et al 2019;Karimi et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…The decrease in the DTPA-extractable Cd observed in the present study after the addition of biochars could be attributed to changes in Cd fractions in the soil. Soil pH strongly influences the reactions and availability of PTEs in calcareous soil (Karimi et al 2019). In comparison to the control treatment, treatments that involved the addition of biochars to soil increased the soil pH in the current study (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Similarly to the present research, Karimi et al (2020) reported that the application of 2% corn residue biochar produced at 500°C decreased DTPA-Zn in a calcareous soil. In other work, Karimi et al (2019) reported that the application of corn residue biochar produced at 500°C increased Zn associated with organic matter and residual fraction in calcareous soil, while exchangeable and associated with Fe-Mn oxide fractions decreased. They reported that the application of corn residue biochar produced at 500°C increased the Zn associated with Fe-Mn oxides when compared with the control.…”
Section: Znmentioning
confidence: 83%